Differences in Carcinoembryonic Antigen (CEA) Levels Based on the Degree of Histopathological Differentiation of Colorectal Cancer: Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Reni Asprilia; Efrida; Syofiati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Colorectal cancer is the third malignancy and second leading cause of death in the world. CEA levels before surgery can be used as a cancer marker to help staging, planning, monitoring therapy and disease recurrence. One factor that influences CEA levels is the degree of differentiation of cancer cells. This study aims to determine differences in CEA levels based on the degree of histopathological differentiation in colorectal cancer patients at Dr. M. Djamil General Hospital Padang. Methods: This study was a cross-sectional analytical observational study using medical record data from colorectal cancer patients from January 2021 – August 2023. The sample was 65 patients who met the inclusion and exclusion criteria. CEA examination uses the ELFA method. The Mann Whitney test was used to see differences in CEA levels based on the degree of differentiation, statistically significant if p < 0.05. Results: A total of 65 patients with an average age of 56.89 years, 58.5% men, 41.5% women. A total of 10 patients were stage I, 29 stage II, and 26 stage III. Based on histopathology, 50 patients were classified as low grade and 15 as high grade. Low-grade CEA levels were 67.72 (3.14-200) ng/mL, while high grade were 3.2 (0.57-11.42) ng/mL. There was a significant difference in CEA levels based on histopathological differentiation (p < 0.001). Conclusion: CEA levels are higher in low-grade than high-grade colorectal cancer.